Resolving the Risk Paradox: Entrepreneurial Cognition in the Lean Startup Method - Ladd, Ted; Kendall, Lori (Journal of Applied Business and Economics, 2017)
The relationships between entrepreneurial orientation and both entrepreneurial intention and entrepreneurial self-efficacy for searching for new ideas strengthen during the Lean Startup Method. Moreover, although the 99 students in a graduate business class did not show a significant change in their traits of aggressiveness, autonomy, and innovativeness, they displayed a significant decline in their proclivity to take risks. These results conclude that the Lean process alters entrepreneurs’ cognition to both increase the likelihood of new venture creation and yet reduce the deleterious impacts of imprudent risk-taking in subsequent decisions.